Comprehensive Estimation of Prerequisites on Creating an Agricultural Cluster in the Akmola Region - OKUTAYEVA, Saule; YESMAGULOVA, Nurgul; SULTANOVA, Aliya; ISKENDIROVA, Saule; JAPAROVA, Kadisha; KUANGALIYEVA, Tursynzada (Journal of Advanced Research in Law and Economics, 2018)
Numerous governmental documents refer clusters to instruments for improving the country’s competitiveness. However, the efficiency of creating them is largely defined by theoretical and methodological approaches to estimating and forming their competitiveness. Due to this, the urgency of considering theoretical and methodological issues of creating competitive clusters through the example of the livestock cluster of Kazakhstan and their impact on the competitiveness of the economy of the Akmola Region is growing. In order to improve the regional policy of the Akmola Region in the livestock sector, it is reasonable to consider the mechanism of uniting all participating entities into a regional meat cluster, the implementation of which can give a powerful impetus to the development of not only the livestock sector in these regions but also to many related industries: trade, processing, transport, etc.